Association between density of convenience and small grocery stores with diet quality in adults living in Mexico City: A cross sectional study - Rodríguez-Guerra, Ana Isabel; López-Olmedo, Nancy; Medina, Catalina; Hernández-Alcaraz, César; Ortega-Avila, Ana G.; Barquera, Simón (Frontiers in Public Health, 2022)
Although there is evidence of the association between different retail stores and food consumption, research is still limited in low- and medium-income countries, where the context of the retail food environment is different to the one observed in high-income countries. Less is known about how convenience stores and small grocery stores, which offer products with immediate access, are associated with the diet as a whole. The present study assessed the association between density of convenience and small grocery stores and diet quality in adults in Mexico City. We analyzed 1,009 adults with data from the Mexico City Representative Diabetes Survey 2015. The density of stores was measured per Euclidean buffers within 500 meters around each participant's home. Diet quality was assessed using the Mexican diet quality index (MxQDI). We performed multivariable Poisson models to test the association of small grocery and convenience store densities with MxQDI. The results showed an inverse association between grocery store density and the overall diet quality among adults living in Mexico City. Specifically, a higher density of small grocery stores was associated with lower fruit and sugar-sweetened beverages (SSBs) intake. We did not observe an association between convenience store density and the overall diet quality. However, the convenience store density was associated with higher intakes of SSBs and sodium. Therefore, small grocery stores may be associated with lower diet quality and convenience stores are linked with a major intake of unhealthy food. This study contributes to new insight and knowledge about the role of these two types of food stores in adopting a healthy diet. In addition, these results provide evidence that supports public health policies aimed at promoting strategies to create healthy food environments.